The evolution of organic food certification - Kononets, Yevhen; Konvalina, Petr; Bartos, Petr; Smetana, Pavel (Frontiers in Sustainable Food Systems, 2023)
The surge in the development of the organic food movement is in response to mass industrial food production, prioritizing productivity and economic profit across the global food supply chain, the cost of individual human health, the nutritional value of products, environmental degradation, and climate change. In recent decades, bio-certified food has become especially important to farmers, consumers, and policymakers as a viable transition away from high-input, intensive farming methods to a more humane and sustainable food system. However, to create value and a point of distinction in the marketplace, a robust and valid operation system to verify organic standards throughout the supply chain is of utmost importance. In this study, we conducted two separate surveys. The first survey targeted active organic farmers from three countries. Based on the data obtained, we confirm, similar to other investigations, that the current system of bio-certification is not reliable with a certain degree of probability. The second survey consulted highly specialized experts in organic systems from around the world to identify how the bio certification system should be transformed. The results indicated that the average probability of unregistered violations can be 35.4% according to self-reporting by organic farmers. This together with results that found that 96.12% of experts believe that the organic certification procedure needs to change provides increasing evidence and justification for an overhaul of the certification system.